A STUDY OF THE BOILOVER PHENOMENON. EXPERIMENTAL DETERMINATION OF MASS BURNING RATE AND BOILOVER TIME (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The phenomenon of “boilover” a catastrophic event characterized by the explosive ejection of burning liquid from heated storage tanks, poses significant safety risks in industrial settings. This study investigates the critical parameters influencing boilover, such as mass burning rate and time to onset, utilizing a meticulously designed experimental apparatus that simulates real-world conditions on a reduced scale. The experiment setup includes a combustion chamber, precise thermocouple arrays for temperature monitoring, and scaled-down oil storage models to replicate the thermal dynamics observed in actual tanks. By observing the combustion process from its initiation to the critical boilover event, this study not only tracks the progressive temperature changes but also identifies specific precursor signals of impending danger. The research employs a combination of direct observation and sophisticated data analysis techniques to dissect the interactions between the burning fuel and the underlying water layer, crucial for understanding the boilover mechanism. Enhanced by mathematical modeling, the findings propose predictive tools that forecast the timing of boilover, enabling preemptive safety measures. Ultimately, this study aims to refine risk assessment practices and improve preventive strategies, thereby safeguarding lives and property against one of the most dramatic threats in fire safety management when handling and storing flammable liquids.